Endothelitis profile in acute heart failure and cardiogenic shock patients: Endocan as a potential novel biomarker and putative therapeutic target - Reina-Couto, Marta; Silva-Pereira, Carolina; Pereira-Terra, Patrícia; Quelhas-Santos, Janete; Bessa, João; Serrão, Paula; Afonso, Joana; Martins, Sandra; Dias, Cláudia Camila; Morato, Manuela; Guimarães, João T; Roncon-Albuquerque, Roberto; et al. (Frontiers in Physiology, 2022)
Aims: Inflammation-driven endothelitis seems to be a hallmark of acute heart failure (AHF) and cardiogenic shock (CS). Endocan, a soluble proteoglycan secreted by the activated endothelium, contributes to inflammation and endothelial dysfunction, but has been scarcely explored in human AHF. We aimed to evaluate serum (S-Endocan) and urinary endocan (U-Endocan) profiles in AHF and CS patients and to correlate them with biomarkers/parameters of inflammation, endothelial activation, cardiovascular dysfunction and prognosis. Methods: Blood and spot urine were collected from patients with AHF (n=23) or CS (n=25) at days 1-2 (admission), 3-4 and 5-8 and from controls (blood donors, n=22) at a single time point. S-Endocan, U-Endocan, serum IL-1β, IL-6, tumour necrosis factor-α (S-TNF-α), intercellular adhesion molecule-1 (S-ICAM-1), vascular cell adhesion molecule-1 (S-VCAM-1) and E-selectin were determined by ELISA or multiplex immunoassays. Serum C-reactive protein (S-CRP), plasma B-type natriuretic peptide (P-BNP) and high-sensitivity troponin I (P-hs-trop I), lactate, urea, creatinine and urinary proteins, as well as prognostic scores (APACHE II, SAPS II) and echocardiographic left ventricular ejection fraction (LVEF) were also evaluated. Results: Admission S-Endocan was higher in both patient groups, with CS presenting greater values than AHF (AHF and CS vs Controls, p<0.001; CS vs AHF, p<0.01). Admission U-Endocan was only higher in CS patients (p<0.01 vs Controls). At admission, S-VCAM-1, S-IL-6 and S-TNF-α were also higher in both patient groups but there were no differences in S-E-selectin and S-IL-1β among the groups, nor in P-BNP, S-CRP or renal function between AHF and CS. Neither endocan nor other endothelial and inflammatory markers were reduced during hospitalization (p>0.05). S-Endocan positively correlated with S-VCAM-1, S-IL-6, S-CRP, APACHE II and SAPS II scores and was positively associated with P-BNP in multivariate analyses. Admission S-Endocan raised in line with LVEF impairment (p=0.008 for linear trend). Conclusions: Admission endocan significantly increases across AHF spectrum. The lack of reduction in endothelial and inflammatory markers throughout hospitalization suggests a perpetuation of endothelial dysfunction and inflammation. S-Endocan appears to be a biomarker of endothelitis and a putative therapeutic target in AHF and CS, given its association with LVEF impairment and P-BNP and its positive correlation with prognostic scores.